A case report of airway stenting in tracheal compression secondary to right subclavian artery pseudo-aneurysm - Abdul Azih, Muhammad Naimmuddin; Ibrahim, Aishah; How, Soon Hin; Chunn, Kuan Yeh (International Islamic University Malaysia, 2018)
We report a 55-year old lady with the presentation of stridor and type II respiratory failure requiring tracheal intubation. She had right Horner’s syndrome associated with pleural effusion. Her chest radiograph revealed right upper zone lobulated opacities and therefore right Pancoast tumor was the initial diagnosis. However, her CECT thorax revealed a huge right subclavian artery pseudoaneurysm with severe tracheal compression. This rare condition imposed a significant diagnostic as well as therapeutic challenge. Vascular surgery is the definitive treatment but it is associated with high risks. The exact role of rigid bronchoscopy for airway stenting is unknown due to limited evidence available. Indeed, this form of central airway obstruction may benefit from temporary tracheal stenting whilst the surgical repair of the lesion is planned. It may facilitate early weaning and allows less complicated airway control.